Analisis Penerapan Aplikasi Berbasis Mobile pada Nom-Nom Cafe Malang Menggunakan Technology Acceptance Model (TAM) - Nanda Dwi Raharjo; Aryo Pinandito; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sales is an important component of business processes. By determining the strategy in the sale and promotion of goods sold, this will certainly impact on profits earned by the company. Nom-Nom cafe is one of the cafes engaged in the sale of food and beverages that stood since the year 2016 ago in the city of Malang. There are enough things that might be done to increase sales from Nom-Nom, by using android-based mobile applications that are expected to increase the number of product sales from Nom-Nom cafe. In this research, tested by multiple linear regression analysis method to determine the factors that influence the intention to user behavior in the transaction of Nom-Nom cafe Application. It needs a method to see the acceptance of this app. TAM is a model used to analyze and understand the factors that affect the acceptance of a computer technology. Then to see if the application can increase sales or not, it can be done by analyze the sales results from before and after the application is applied. The results of this research show that only one rejected hypothesis from the test results and the results of sales analysis shows that the Nom-Nom application increase the sales of Nom-Nom cafÃ© product